STRATEGI PENGEMBANGAN DESTINASI PARIWISATA PANTAI TANJUNG API DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA SEBUBUS KECAMATAN PALOH KABUPATEN SAMBAS PERSPEKTIF EKONOMI ISLAM - Arini; Hutagaluh, Oskar; Sulia Sukmawati, U (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study employs a descriptive qualitative approach and is categorized as field research. The data collection techniques used include observation, interviews, and documentation. The sources of data in this study are divided into primary and secondary sources. The primary data sources consist of tourism managers, including local community members and business operators, while the secondary data source is the village head. The data analysis techniques used in this research include data reduction, data presentation, and conclusion drawing. The validity of the data is ensured through triangulation. Based on the research findings, it is concluded that the development strategy of Tanjung Api Beach tourism in improving the community’s economy in Sebubus Village from an Islamic economic perspective has contributed to increasing income through trade and business opportunities in the tourism area. It has also led to a shift in professions, with some community members transitioning from farming to trading. In the tourism development process, visitors are prohibited from engaging in activities that violate Islamic principles. The development of Tanjung Api Beach tourism has had a positive economic impact, particularly on residents living near the tourism area.